Analisis Daya Tahan Kardiovaskuler pada Kelompok Senam Hip Heart Siswa SMAN 4 Pangkep - Anggraeni, Emayanti (Jurnal Muara Olahraga, 2024)
Hip Heart Gymnastics is a gymnastics created by the Healthy Heart Foundation which is intended for Indonesian teenagers so that they know how important it is to care for and maintain the Heart. aims to determine Cardiovascular Endurance in the Hip Heart Gymnastics Group of Students at SMAN 4 Pangkep. This research is a quantitative research with a quantitative description method. The subjects in this study amounted to 50 people with a sample of 30 people (N = 30), 30 people are female students who join the gymnastics group, have participated in gymnastics competitions, and members of the Hip Heart gymnastics group. The data collection technique in the study used a test, namely the Bleep test with the Purposive Sampling technique. Description Analysis obtained a total value of Ʃ = 738.6, average X = 24.67, Std = 2.30, Max = 28.7 and Min = 20.0. And the results of the study using the Liliefors Test showed that cardiovascular endurance in the Hip heart gymnastics group of SMAN 4 Pangkep (α = 0.05) obtained Lh of = 0.079 and Lt (0.05) = 0.161, thus because Lh is smaller than Lt (0.05) then Normally Distributed. From the results of cardiovascular endurance in the Hip heart gymnastics group of SMAN 4 Pangkep students showed in the interval class 26.4 - 27.9, with a frequency of 9 students with a presentation of 26.66%. study of Cardiovascular Endurance in the Hip Heart Gymnastics group at SMAN 4 Pangkep showed conditions or categories from good to very good.